2014
DOI: 10.2147/ott.s67217
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of micro-ribonucleic acid-128 cooperating with downregulation of PTEN confers metastatic potential and unfavorable prognosis in patients with primary osteosarcoma

Abstract: ObjectiveAbnormal expression of micro-ribonucleic acid (miRNA [miR])-128 has been observed in various human cancer types, and its validated target genes are implicated in cancer-related cellular processes, such as cell proliferation, differentiation, and apoptosis. Especially, it has been demonstrated that miR-128 may play an important role in the proliferation of human osteosarcoma cells in vitro by directly inhibiting PTEN, which functions as a tumor suppressor in this malignancy. In the current study, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…PTEN has many important functions in the body, such as the inhibition of cell growth and differentiation (14) and promotion of cell apoptosis (15), making it one of the most noticeable tumor suppressor genes after the p53 gene. NF-κB is a transcription factor with a two-way transcriptional regulation that plays an important role in many pathophysiological processes (1618). Loftus et al (19) reported a significant increase in NF-κB p65 expression in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN has many important functions in the body, such as the inhibition of cell growth and differentiation (14) and promotion of cell apoptosis (15), making it one of the most noticeable tumor suppressor genes after the p53 gene. NF-κB is a transcription factor with a two-way transcriptional regulation that plays an important role in many pathophysiological processes (1618). Loftus et al (19) reported a significant increase in NF-κB p65 expression in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous tumor biopsy-based markers have been found for OS and include miR-9, miR-132, miR-145, miR-183, miR-223, and miR-128 in combination with transcript levels of phosphatase and tensin homolog ( PTEN ) (3439), the DNA mismatch repair proteins MutS protein homolog 2 (MSH2) and MSH6 (40), hypermethylated DNA of ARF tumor suppressor (p14 ARF ) and estrogen receptor α (41), the transcription factor SOX9 (42), RAC-β serine/threonine-protein kinase (AKT2) (43), periostin (44), neuropilin-1 (45), glucose transporter protein 1 (GLUT-1) (46), and polymeric immunoglobulin receptor (pIgR) (47), amongst others. However, these markers are derived from the primary OS site and therefore discount metastases, which are important determinants for PFS (9,12,13).…”
Section: Discussionmentioning
confidence: 99%
“… 4 In our previous studies, we demonstrated that the deregulation of three miRNA/mRNA combinations, including miR-128/target gene PTEN, miR-223/target gene epithelial cell transforming sequence 2, and miR-183/target gene Ezrin axes, were significantly associated with the aggressive progression of human osteosarcoma. 5 7 More interestingly, these combinations may function as potential prognostic markers for patients with this malignancy. 5 7 However, the exact mechanisms of this malignancy remain unclear, thereby posing great challenges to its clinical treatment.…”
Section: Introductionmentioning
confidence: 99%